Role of teachers in achieving distance learning outcomes - Nadya Prameski Putri; Lu'luil Maknun (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2021)
The purpose of this research was to analyze the important role of educators in the achievement of distance learning outcomes at MI Al-Mursyidiyyah. The method used is the mixing method, where the sources studied come from the results of the literature review and the results of questionnaire processing. The results of the questionnaire processing and literature review provided 3 important discussion points, namely; (1) PJJ (Distance Learning), (2) The Role of Teachers in Distance Learning and, (3) Criteria for Achievement of Learning Outcomes. Seeing the current situation, the role of educators must be optimized so that they can carry out their roles and the learning process properly. Educators not only convey material, but also must be able to design a learning process that is as attractive as possible by using learning media such as online games and so on, so that educators can attract the attention of students so that they remain enthusiastic in the learning process.